2011
DOI: 10.1016/j.ic.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic proofs over noncommutative formulas

Abstract: We study possible formulations of algebraic propositional proof systems operating with noncommutative formulas. We observe that a simple formulation gives rise to systems at least as strong as Frege-yielding a semantic way to define a Cook-Reckhow (i.e., polynomially verifiable) algebraic analog of Frege proofs, different from that given in [BIK + 97, GH03]. We then turn to an apparently weaker system, namely, polynomial calculus (PC) where polynomials are written as ordered formulas (PC over ordered formulas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…In a sequence of more recent papers, polynomial identity testing algorithms were devised for roABPs ([64, 25, 27, 24, 2], see also Section 3.1). In terms of proof complexity, Tzameret [83] studied a proof system with lines given by roABPs, and recently Li, Tzameret and Wang [50] (Theorem 1.4) showed that IPS over non-commutative formulas is essentially equivalent in power to the Frege proof system. Due to the close connections between non-commutative ABPs and roABPs, this last result suggests the importance of proving lower bounds for roABP-IPS as a way of attacking lower bounds for the Frege proof system (although we obtain roABP-IPS LIN lower bounds without obtaining non-commutative-IPS LIN lower bounds).…”
Section: Oblivious Algebraic Branching Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a sequence of more recent papers, polynomial identity testing algorithms were devised for roABPs ([64, 25, 27, 24, 2], see also Section 3.1). In terms of proof complexity, Tzameret [83] studied a proof system with lines given by roABPs, and recently Li, Tzameret and Wang [50] (Theorem 1.4) showed that IPS over non-commutative formulas is essentially equivalent in power to the Frege proof system. Due to the close connections between non-commutative ABPs and roABPs, this last result suggests the importance of proving lower bounds for roABP-IPS as a way of attacking lower bounds for the Frege proof system (although we obtain roABP-IPS LIN lower bounds without obtaining non-commutative-IPS LIN lower bounds).…”
Section: Oblivious Algebraic Branching Programsmentioning
confidence: 99%
“…In Appendix A we describe various other algebraic proof systems and their relations to IPS, such as the dynamic Polynomial Calculus of Clegg, Edmonds, and Impagliazzo [13], the ordered formula proofs of Tzameret [83], and the multilinear proofs of Raz and Tzameret [66]. In Appendix B we give an explicit description of a multilinear polynomial occurring in our IPS upper bounds.…”
Section: Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Raz and Tzameret [RT08b,RT08a,Tza08] investigated algebraic proof systems operating with multilinear formulas, motivated by lower bounds on multilinear formulas for the determinant, permanent and other explicit polynomials [Raz09,Raz06]. Atserias et al [AKV04], Krajíček [Kra08] and Segerlind [Seg07] have considered proofs operating with ordered binary decision diagrams (OBDDs), and the second author [Tza11] initiated the study of proofs operating with non-commutative formulas (see Sec. 1.4 for a comparison with the current work).…”
Section: Prominent Directions For Understanding Propositional Proofsmentioning
confidence: 99%
“…Let us also mention the work in [Tza11] that dealt with propositional proof systems over noncommutative formulas. In [Tza11] the choice was made to define all proof systems as polynomial calculus-style systems in which proof-lines are written as non-commutative formulas (as well as the more restricted class of ordered-formulas). This meant that the characterization of a proof system in terms of a single non-commutative polynomial is lacking from that work (as well as the consequences we obtained in the current work).…”
Section: Comparison With Previous Workmentioning
confidence: 99%